2022
DOI: 10.1177/08862605221090568
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Investigation of the Association between Betrayal Trauma and Dissociative Features

Abstract: Betrayal trauma theory proposes that betrayal and non-betrayal traumas are different in terms of their nature and impacts. The theory predicts that dissociation is more strongly related to betrayal than to non-betrayal trauma, however there is a lack of cross-cultural evaluation of the theory. One competing theory is the socio-cognitive model, which proposes that dissociative amnesia (DA) and identity dissociation (ID) are the results of social influence and are not trauma-related conditions. This study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Especially in the context of childhood betrayal trauma (i.e. trauma perpetrated by someone with whom the victim is close to; for example, physical or sexual abuse by a trusted person) (Freyd, 2008;Freyd et al, 2007), the survivors may develop more dissociative and borderline personality symptoms that could affect their interpersonal relationships (Fung et al, 2022a;Zamir et al, 2018). Moreover, one's exposure to betrayal trauma may particularly imply that there is an ongoing stressful interpersonal environment because the persons he or she relied on were the perpetrators.…”
mentioning
confidence: 99%
“…Especially in the context of childhood betrayal trauma (i.e. trauma perpetrated by someone with whom the victim is close to; for example, physical or sexual abuse by a trusted person) (Freyd, 2008;Freyd et al, 2007), the survivors may develop more dissociative and borderline personality symptoms that could affect their interpersonal relationships (Fung et al, 2022a;Zamir et al, 2018). Moreover, one's exposure to betrayal trauma may particularly imply that there is an ongoing stressful interpersonal environment because the persons he or she relied on were the perpetrators.…”
mentioning
confidence: 99%
“…Although the reliability and validity of dissociation have been evaluated and established for decades (Mychailyszyn et al, 2021; Ross et al, 2002; Van IJzendoorn & Schuengel, 1996), and although dissociation has long been conceptualized as a response to trauma (Dalenberg et al, 2012; Fung et al, 2023; Putnam, 1985; Van der Hart et al, 2006), which highlights the importance of child protection, dissociation remains a controversial topic in terms of its prevalence, cross-cultural validity, and etiological factors. To resolve theoretical uncertainties and inform clinical assessments and interventions, some major knowledge gaps require further investigation and discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of dissociative amnesia and identity dissociation have been associated with cross-cultural childhood betrayal trauma. 8 Known since 1800s, DID is a psychiatric disorder that is highly recognisable under the category of dissociative disorders and accompanied by memory and identity disorders. 9 Research indicates that dissociative disorders are observed in 12-13.8% of the psychiatric patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of dissociative amnesia and identity dissociation have been associated with cross-cultural childhood betrayal trauma. 8 …”
Section: Introductionmentioning
confidence: 99%